Comparison of fitness components between state and national volleyball players in Malaysia - Shahrin, Nur Shafiqah Mohd (Universiti Sains Malaysia, 2016)
The determination of fitness components of athletes has been popular over last few decades. As a volleyball player, they need to have a well developed physical fitness to enable successful performance at the competitive level. However, in Malaysia, there is limited information regarding the fitness components among volleyball players. Therefore the objective of the study was to determine the difference of fitness component between state and national volleyball players (men’s and women’s). Twenty eight state players (gender: 14 males and 14 females ; age: 19.4 ± 1.2 years respectively , 18.3 ±1.2 years respectively) and 24 national players (gender: 12 males and 12 females ; age: 22.8 ±1.4 years respectively , 21.3 ± 1.1 years respectively ) participated in this research. Health and skill related fitness components were assessed. The health-related fitness includes cardiovascular fitness, flexibility, body composition and muscle strength and muscle endurance. Meanwhile, the skill-related fitness component are agility, speed and power. Independent Sample T-test was used to analyses the differences of all physical fitness components between the state and the national players. Results showed that, the men’s national team, heavier compared to state players, while state players revealed that they are faster compared to the national players. While for women’s national team, the players are taller, heavier and agile compared to the state players. The result showed that training and playing experienced influenced the agility in the court. In conclusion, there are a lot of other factors that may contribute to an individual performance apart from their fitness component. However, information gained from this study can be a benchmark for future team fitness component in order to maintain well establishes fitness level to optimize performance.